Recall and Precision Temu Kembali Informasi Pada Repository Universitas Negeri Padang - Auwiyah, Windi; Erlianti, Gustina (Innovative: Journal Of Social Science Research, 2025)
This study aims to evaluate the effectiveness of the search system in the Universitas Negeri Padang repository through three indicators, namely recall, precision, and F-measure. The method used is a descriptive quantitative approach by testing 75 keywords from eight study programs. The results show that the system has a very high recall, which is 100%, an average precision of only 34.48% and an F-measure of 43.09%. This shows that the system is able to reach all relevant documents, but is less accurate in displaying results that meet user needs. The conclusion of this study is that the effectiveness of the system is less than optimal and needs further development. Suggestions given include improving the quality of metadata, utilizing advanced search features, and developing a context-based search system to be more effective in supporting academic activities.